Digitalization of Religious Content: The Disruption of Ulama Authority in Indonesia - Al-Razi, Muhammad Fakhruddin (Proceeding International Conference on Religion, Science and Education, 2024)
Ulama plays an important role in the religious life of the community. Many religious affairs have relied on ulama as figures who are considered to hold religious authority in the community. Even in the setting of life in Indonesia, ulama not only has a position in the religious field but also in various aspects of life such as economics, politics, and so on. However, since the emergence of the Industrial Revolution 4.0 era, the central role of the ulama has gradually shifted until it was disrupted. This disruption arises due to the process of digitizing religious content that has recently become more prevalent on the internet. Many parties have produced religious content in cyberspace, which in turn has become people's preference in seeking religious information. From this phenomenon, this article states that at this time the role of ulama has been increasingly distorted and replaced by other things such as the internet.